Diversity of genomic clusters and CfiA/cfiA alleles in Bacteroides fragilis isolates from human and animals. (June 2022) - Cao, Huiluo; Liu, Melissa Chun-Jiao; Tong, Man-Ki; Jiang, Shuo; Lau, Andes; Chow, Kin-Hung; Tse, Cindy Wing-Sze; Ho, Pak-Leung
Abstract: Objectives: To compare the phylogeny of cfiA -positive Bacteroides fragilis isolates from diverse human and animal sources. Method: Complete genome sequences were obtained from 42 cfiA -positive B. fragilis isolates (Hong Kong, 2015–2017) and additional 24 genomes deposited in the GenBank (multiple countries, 1985–2019) were included. The genomic clusters were constructed using PopPUNK. The CfiA alleles and polymorphism in the cfiA locus were analyzed in silico. Results: The 66 isolates were grouped into 12 genomic clusters (BFSC-1 to 12). Human infection isolates were distributed in diverse clusters, being many of them common to fecal isolates from both human and animals. Thirteen CfiA alleles including 2 novel ones were identified. CfiA-1 (n = 28) is the predominating allele, following by CfiA-13 (n = 8), CfiA-4 (n = 7) and CfiA-14 (n = 6). The other CfiA alleles were identified in 1–3 isolates. Six patterns of gene context were identified in the regions flanking cfiA locus. No consistent association between genomic clusters and CfiA alleles could be detected. Similarly, markedly elevated imipenem MIC was linked to the integration, immediately upstram of cfiA of an IS element but not the CfiA allele or gene context. Conclusion: The phylogeny of cfiA -positive B. fragilis isolates causing human diseases was diverse and overlaped with those from human and animal carriage. Highlights: The genomic phylogeny of 66 cfiA -positive Bacteroides fragilis isolates was analyzed. The isolates were grouped into 12 PopPUNK-based genomic clusters. Clinical isolates shared the same genome clusters as carriage isolates from human and animals. No correlation between CfiA allele and genome cluster was identifed. The phylogeny of emerging cfiA -positive B. fragilis is diverse.